Maxillary protraction with bimaxillary bone anchor and mini rigid surgical fixation plates in patient with Bilateral Cleft Lip and Palate Sequelae: Case report - Acosta Rangel Monica C; Ayuso Arce América; Amador Jiménez Olaf (International Journal of Oral and Craniofacial Science - Peertechz Publications, 2018)
The objective is to evaluate the effects of maxillary protraction by means of a bimaxillary bone anchorage as well as its progress by fixing mini plates in patients with Bilateral Cleft Lip and Palate Sequela, based on the protocol of Clerck and Cha et al. HGO CM La Raza and the Technological University of Mexico UNITEC.